Single room versus open-bay design in neonatal intensive care units for improvement in infant outcomes: a systematic review protocol. (October 2017) - Disher, Timothy; Dol, Justine; Richardson, Brianna; Campbell-Yeo, Marsha
Abstract : Review question/objective: : The objective of this review is to identify the impact of single room neonatal intensive care unit (NICU) design on infant outcomes compared to alternative design. The specific question is: what is the impact of single room design on outcomes of infants cared for in intensive care units compared to those in alternative designs?